THE POTENTIAL OF POLLARD AND RICE BRAN WITH FRACTIONATION PROCESS AS RAW MATERIALS FOR HIGH FIBER PROCESSED FOOD - Ainun Nafisah; Nahrowi Nahrowi (University of Sultan Ageng Tirtayasa, 2021)
Rice bran and pollard are by-products of the rice and wheat milling process. These two ingredients are generally not used as the main raw material for food products and are diverted as feed ingredients due to their low nutritional content. The nutrient content that is still present in pollard and rice bran, especially fiber and anti-nutrients, is very useful for people with diabetes and obesity. The purpose of this study was to analyze the effect of sifting and fractionation on nutrient content and to separate the components of pollard and rice bran using a gravity and molecular weight approach. The experimental design used was CRD (Completely Random Design) Factorial 2 × 3 × 3 for physical test data. Factor A is the material, namely pollard and rice bran, factor B is the position of the fraction, namely top, middle and bottom. Data analysis was performed by analysis of variance (ANOVA) and the significant one will be further analyzed using Duncan's test. The chemical property values were analyzed descriptively. The results showed that the value of bulk density (g l-1), compacted bulk density (g l-1), specific gravity (kg l-1), angle of purpose (o) of pollard and rice bran were significantly different (P<0.05) on all three fractions. The highest physical parameters for pollard were at the bottom fraction with the value 386.47 g g l-1, 537.28 g l-1, 1.42 kg l-1, ST 46.98o. The highest physical parameters for rice bran were at the upper fraction with the value of 394.09 g l-1, 526.33 g l-1, 1.50 kg l-1, ST 46.01o. Crude fiber content (%) of pollard and rice bran were the upper fractions 6.77 and 21.69, middle fractions 8.19 and 34.70, lower fractions 5.52 and 32.76. Fractionation technology can separate food ingredients based on chemical components, especially crude fiber with a molecular weight approach so that it can be seen whether the position of the fraction can be optimized or not as a raw material for making high-fiber biscuits. Physical and chemical properties of pollard and rice bran were best in the lower and upper fractions.